Transporter-mediated Natural Product-Drug Interactions - Bi, Yajuan; Wang, Xue; Ding, Hui; He, Feng; Han, Lifeng; Zhang, Youcai (Planta Medica, 2022)
The increasing use of natural products in clinical practice has raised great concerns about the potential natural product-drug interactions (NDIs). Drug transporters mediate the transmembrane passage of a broad range of drugs, and thus are important determinants for drug pharmacokinetics and pharmacodynamics. Generally, transporters can be divided into ATP binding cassette (ABC) family and solute carrier (SLC) family. Numerous natural products have been identified as inhibitors, substrates, inducers, and/or activators of drug transporters. This review article aims to provide a comprehensive summary of the recent progress on the research of NDIs, focusing on the main drug transporters, such as P-glycoprotein (P-gp), breast cancer resistance protein (BCRP), organic anion transporter 1 and 3 (OAT1/OAT3), organic anion-transporting polypeptide 1B1 and 1B3 (OATP1B1/OATP1B3), organic cation transporter 2 (OCT2), multidrug and toxin extrusion protein 1 and 2-K (MATE1/MATE2-K). Additionally, the challenges and strategies of studying NDIs are also discussed.
Keywords: natural products; drug transporters; natural product-drug interactions; solute carrier transporter; ATP-binding cassette transporter